Studi Awal Penghapusan Sistem Pemeringkatan: Perspektif Manajemen di Sebuah Kantor Cabang Bri Kota Semarang - Praduganti, Maretha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effectiveness of eliminating the employee ranking system from a management perspective at a BRI branch office in Semarang City, focusing on individual and organizational factors that influence human resource (HR) performance. The research method used was a mixed quantitative and qualitative approach using the Analytical Hierarchy Process (AHP) to assess the weight and priority of personality and organizational criteria for improving employee performance. The results showed that organizational criteria were weighted higher than personality, with the highest scores for the fairness and motivation sub-criteria. Scenario analysis showed that maintaining the ranking system was more effective in improving employee performance, with the organizational criterion weighting 0.603 compared to 0.397 in the elimination scenario. The conclusion is that employee performance improvement strategies should focus on strengthening fair, transparent, and collaborative organizational aspects, along with developing personality aspects according to the needs of each position. Keywords: Employee Performance, Ranking System, Analytical Hierarchy Process (AHP)